If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7 + -2k) = 57 (7 * 3 + -2k * 3) = 57 (21 + -6k) = 57 Solving 21 + -6k = 57 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -6k = 57 + -21 Combine like terms: 21 + -21 = 0 0 + -6k = 57 + -21 -6k = 57 + -21 Combine like terms: 57 + -21 = 36 -6k = 36 Divide each side by '-6'. k = -6 Simplifying k = -6
| -8+4m^2-5m^2= | | 7x+3-2x+9=47 | | z-8.4=4 | | (x+(2+i))(x+(2-i))=0 | | -0.2(212-h)=8.6 | | 5x-10=39 | | 5.25b=22.75 | | -5x-2=-x-7 | | 3(x+1)+3(x+3)= | | 14x-(4x-5)=45 | | 7x-26=2x+54 | | -7(5k-5)=-210 | | 25-3u=24 | | 95=5X+2X+7 | | 2=10-1.6d | | 95=5X+2X+7 | | 95=5X+2X+6 | | 95=5X+2X+6 | | 5x-3(x-5)=-8+4x+17 | | 95=5X+2X+6 | | 6u-40=3(u+4)-4 | | 6u-40=3(u+4)-4 | | 8(10+3+5v)-2v= | | 5y-35x=-35 | | 2+4g=5+1g | | 5u+5=-26u | | 3x-30=3x-9 | | (3r+8)=(r-4) | | n+6=9*5 | | 3x-30+6-15=3x-9 | | 3r^2-5r=-10 | | 2k^12+19k^6-33=0 |